Let the user speak: Is feedback on Facebook a source of firms' innovation? - Irene Bertschek; Reinhold Kesler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
Social media open up new possibilities for firms to exploit information from various external sources. Does this information help firms to become more innovative? Combining firm-level survey data with information from firms' Facebook pages, we study the role that firms' and users' activities on Facebook play in the innovation process. We find that firms' adoption of a Facebook page as well as feedback from users are positively and significantly related to product innovations. Analysis of the content of Facebook posts and comments reveals that firms are more likely to introduce product innovations if they actively ask for feedback, while only negative user comments are positively and significantly related to innovation success. These results withstand a large set of robustness checks, including estimations that take potential endogeneity of firms' Facebook use into account.
Keywords: D22; L23; O31; 330; social media; knowledge sources; product innovation